MANAGEMENT CONFLICT STYLE TOWARDS PRISONER CONFLICTS AT BEKASI CLASS IIA CORRECTIONAL INSTITUTION - Putra, Ferinando Fachrudin; Rahayu, Mulyani (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study explores the causes of inmate conflicts and the role of leadership in conflict management at Bekasi Class IIA Correctional Institution. Using qualitative methods, data were collected through interviews and document analysis. The findings suggest that overcrowding, lack of resources, and inadequate management practices are key contributors to conflicts. Effective leadership and conflict management strategies, including collaboration and compromise, were essential in maintaining order. Keywords: Conflict Management; Prisoner; Role of Leadership